Impact of Service Quality Factors in the Perceived Welfare among Customers of Public Services in the UAE - Alnuaimi, Muna Othman Eissa Othman; Ismail, Norafidah; Packeer, Syed Sultan Bee binti (South Asian Journal of Social Sciences and Humanities, 2021)
The study aims to examine the impact of the five different service quality dimensions on customer welfare in the UAE. The five service quality dimensions are tangible, reliability, responsiveness, assurance, and empathy. The proposed model has five independent variables and one dependent variable. The study has five direct relations. The following is a discussion of the hypothesis development. The study is a scientific study and designed as a quantitative mono-method based on original data collected by the use of a questionnaire and statistical analysis by using PLS-SEM Techniques. The population includes 8 million cases, and the sample size based on the Morgan table is 384. Three cities are chosen based on the population size, as it is the main and most populated city. However, in every city, data collection will take place in main commercial locations, public areas such as parks, malls, etc., or could be collected online. The results show that tangibility and reliability have no significant impact, but the other three dimensions have.